2008
DOI: 10.1007/s00787-008-0705-9
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine versus methylphenidate in treatment of children and adolescents with attention deficit-hyperactivity disorder

Abstract: The study revealed that reboxetine may be beneficial in treatment of ADHD. Further studies are required to clarify the potential therapeutic effects on comorbid depression and anxiety and adverse effect profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…There was also a significant interaction of time (duration of the study) and group (reboxetine vs. placebo) on all subscales of CAARS indices. This finding is consistent with the findings of studies done on children and adolescents (Ratner et al, 2005;Tehrani Doost et al, 2008;Arabgol et al, 2009). Moreover, the results of CGI-S also showed that reboxetine could improve significantly the clinical manifestations of ADHD at the end point of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was also a significant interaction of time (duration of the study) and group (reboxetine vs. placebo) on all subscales of CAARS indices. This finding is consistent with the findings of studies done on children and adolescents (Ratner et al, 2005;Tehrani Doost et al, 2008;Arabgol et al, 2009). Moreover, the results of CGI-S also showed that reboxetine could improve significantly the clinical manifestations of ADHD at the end point of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Reboxetine is another SNRI which has been studied in some clinical trials in reducing ADHD symptoms in children and adolescents (Okta and Mercadante, 2004;Mozes et al, 2005;Ratner et al, 2005;Cak, 2006;Ç ak and Ç etin, 2006;Toren, 2007;Tehrani Doost et al, 2008;Arabgol et al, 2009). The profile of adverse events of reboxetine are low and there is no risk of potential abuse (Ratner et al, 2005;Toren, 2007;Tehrani Doost et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These include the noradrenaline specific re-uptake inhibitor (NaRI), atomoxetine and alpha 2 -adrenoceptor agonist, guanfacine (Kratochvil et al 2003;Kratochvil et al 2006;Wilens 2006;Arnsten et al 2007;Vaughan et al 2009). In addition, the tricyclic antidepressant, desipramine and NaRI, and antidepressant, reboxetine have been reported to show efficacy in ADHD (Wilens 2006;Arabgol et al 2009). This spectrum of drugs shows benefits in terms of attentional impairments and impulsivity and suggests an important role for the catecholamine transmitters dopamine and noradrenaline in the treatment of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of atomoxetine to increase cortical dopamine is thought to arise from the non-selective uptake of dopamine by the NAT in regions receiving noradrenergic innervations (Carboni and Silvagni 2004). Atomoxetine has been shown to improve symptoms of ADHD in adults and children as well as studies showing beneficial effects on impulse control in normal volunteers (Arabgol et al 2009;Chamberlain et al 2006a). In animal studies, atomoxetine treatment improved impulse control in three different animal models, the five-choice serial reaction time task (5CSRTT), stop signal reaction time task and delayed reward (Robinson et al 2008;Bari et al 2009) indicating atomoxetine consistently improved different types of impulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…The positive response to reboxetine in our patients is similar to the findings reported in previous studies in pediatric patients without ASD with MDD or ADHD. 24,26,33 Atomoxetine, another NRI, was found to be effective and safe treatment for ADHD in adolescents with ADHD and MDD. 33 Ratner et al 24 reported significant improvement (P G 0.01) in comorbid depressive symptoms in adolescents with ADHD treated with reboxetine.…”
Section: Discussionmentioning
confidence: 99%